KAJIAN BIBLIOMETRIK PRODUK KOMBINASI HIDROGEL-OLEOGEL (BIGELS) - Febriansyah, Muhammad Irfan; Puteri, Nafisah Eka (Program Studi Ilmu Teknologi Pangan Universitas Muhadi Setiabudi, 2025)
Bigels, which are colloidal systems combining oleogel and hydrogel, demonstrate significant potential in the delivery and release of bioactive compounds, offering better physicochemical stability compared to emulsions and other gels. Bigels are capable of simultaneously transporting both lipophilic and hydrophilic components, making them ideal for applications in cosmetic, pharmaceutical, and food products. However, their development faces challenges such as the limited availability of safe oleogelators, the need to optimize rheological properties, and consumer acceptance. This study aims to conduct a bibliometric review to map the research trends on bigels, identify dominant topics, and analyze the latest developments in this field. Publication data was collected using the term